2009
DOI: 10.1038/ajg.2009.332
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Endothelial Progenitor Cell Number and Function in Inflammatory Bowel Disease: A Possible Link to the Pathogenesis

Abstract: We hypothesize that in IBD patients, apoptosis contributes to the reduction of circulating EPC number and to their ability to proliferate in vitro. As this condition represents a risk factor for cardiovascular disease, endothelial function should be evaluated in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 67 publications
1
35
0
2
Order By: Relevance
“…To eliminate this difficult transition, we have always used human cells throughout our initial research. However, multiple studies have clearly demonstrated that donor age and health status can dramatically affect cell behavior [Phillips et al, 1994;Becerra et al, 1996;Michel et al, 1996;Mogford et al, 2002;Heeschen et al, 2004;Zhang et al, 2005;Garolla et al, 2009;Krenning et al, 2009;Westerweel and Verhaar, 2009]. Thus, the second translational step was to use age-and risk-matched human cells.…”
Section: Preclinical Studies With the Lifeline Tm Graftmentioning
confidence: 99%
“…To eliminate this difficult transition, we have always used human cells throughout our initial research. However, multiple studies have clearly demonstrated that donor age and health status can dramatically affect cell behavior [Phillips et al, 1994;Becerra et al, 1996;Michel et al, 1996;Mogford et al, 2002;Heeschen et al, 2004;Zhang et al, 2005;Garolla et al, 2009;Krenning et al, 2009;Westerweel and Verhaar, 2009]. Thus, the second translational step was to use age-and risk-matched human cells.…”
Section: Preclinical Studies With the Lifeline Tm Graftmentioning
confidence: 99%
“…Garolla et al [1] reported a lower number of circulating EPCs in CD patients compared to controls, demonstrating that apoptosis is the principal pathway for EPC reduction. Contrary to the previous study, Masuda et al [9] reported no significant reduction in the number of circulating EPCs among CD patients as compared to controls.…”
mentioning
confidence: 99%
“…T cells, expansion of the intestinal microvasculature, and endothelial impairment [1,2]. Approximately 565,000 residents of the USA are diagnosed with CD each year.…”
mentioning
confidence: 99%
See 2 more Smart Citations